Legal Enforcement and the Recovery of State Financial Losses in Corruption Crimes: A Normative and Institutional Review - Lestari, Ditha; Metha Dian Puspa Nasawida (Eastasouth Institute, 2025)
Corruption is a systemic crime that demands comprehensive legal reform efforts. This study analyzes the impact and obstacles of recovering state financial losses due to corruption within the framework of legal enforcement based on audit findings from the Indonesian Supreme Audit Agency (BPK). Using a normative juridical method, this research focuses on secondary data derived from laws, legal principles, and related literature. The findings indicate that the recovery of state financial losses, although important, does not eliminate the criminal nature of corruption under Indonesian criminal law. Offenders are still subject to criminal proceedings regardless of restitution. However, the process faces several systemic challenges, including regulatory inconsistencies, bureaucratic complexity in handling cases involving state officials, and the lack of clear operational mechanisms among law enforcement institutions such as the National Police, Attorney General’s Office, BPK, and the Financial Transaction Reports and Analysis Center (PPATK). These institutional and normative obstacles hinder the effectiveness of corruption law enforcement and asset recovery efforts. The study recommends strengthening inter-agency coordination, harmonizing legal provisions, and simplifying procedural requirements to ensure effective and efficient enforcement of anti-corruption measures. Ultimately, a more integrated legal system is essential to uphold justice and safeguard public assets from corrupt practices.